Pupuk Kandang Ayam dan Pupuk Organik Cair (POC) Kulit Pisang terhadap Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L.) - M. Ocky Andrean Syahputra; Farida Hariani; Erlita Chaniago (Jurnal Agrofolium, 2023)
The purpose of this study was to determine the application of chicken manure and liquid organic fertilizer (POC) banana peels on the growth and production of shallots (Allium ascalonicum L.) and their interactions. This study used a factorial randomized block design with 2 factors studied and 3 replications where the first factor was chicken manure (A) consisting of 4 levels, namely A0 = no treatment (control), A1 = 1.4 kg plot-1 (20 tons ha-1), A2 = 2.8 kg plot-1 (40 tons ha-1) and A3 = 4.2 kg plot-1. The second factor is liquid organic fertilizer (POC) banana peel (P) consisting of 3 levels, namely P0 = no treatment (control), P1 = 150 ml liter-1 of water, P2 = 300 ml liter-1 of water. Parameters observed were plant height (cm), number of tillers (clump), weight of fresh tuber plant-1 (g), and weight of fresh tuber plot-1 (g). The results showed that the application of chicken manure had a very significant effect on the parameters of plant height, significantly on the parameters of the number of tillers, weight of fresh tubers plant-1, and weight of fresh tubers plot-1.